Superalloys 1988 (Sixth International Symposium) 1988
DOI: 10.7449/1988/superalloys_1988_653_662
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mechanisms Responsible for Degredation in Thin-Wall Stress-Rupture Properties

Abstract: A series of critical experiments was performed on single crystal CMSX-3 and equiaxed grain Mar-M246 specimens to identify the mechanisms responsible for the degradation in stress-rupture properties of 0.020 in. thick mini-flats machined from airfoils compared with 0.250 in. diameter standard test bars.Both materials exhibited approximately a factor of 3X life degradation at a stress level of 20,000 lb/in.2, when uncoated airfoil mini-flats were tested in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 1 publication
0
34
0
Order By: Relevance
“…The time to reach 1% creep strain is more reliable to reveal tendencies than creep rupture lives. It is mentioned in [3,4,6] that the time to reach 1% strain is independent of wall-thickness. This is the case in our tests only for the higher stress level of 300 MPa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The time to reach 1% creep strain is more reliable to reveal tendencies than creep rupture lives. It is mentioned in [3,4,6] that the time to reach 1% strain is independent of wall-thickness. This is the case in our tests only for the higher stress level of 300 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…For the polycrystalline nickel-base superalloy PWA 1484 Duhl [1] found a five fold reduction of creep rupture life if the specimen thickness is diminishing from 4 to 0.5 mm which mainly depends on grain size and micro structural defects. Doner and Heckler [3,4] observed in uncoated single crystal CMSX-3 a 30% loss in creep rupture life if the wall thickness was reduced from 3.18 to 0.76 mm at 982°C and if the stress level was below 275 MPa. They also found that the time to reach 1% strain was unaffected by wall thickness at a constant stress level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to optimize both the cooling efficiency and the weight of fast rotating turbine blades a general trend is to reduce the wall thickness of the hollow investment casting parts. It has been shown that reducing the wall thickness leaded to lower lifetimes and higher minimum creep rates [16][17][18]. Besides in the case of thin-coated specimens it could be explained at least partly by the reduction of the load bearing because of the interdiffusion between coating and superalloy [18].…”
Section: Introductionmentioning
confidence: 99%